Experimental Demonstration of Nanoscale Pillar Phononic Crystal-Based Reflector for Surface Acoustic Wave Devices - Temesgen Bailie Workie; Lingqin Zhang; Junyao Shen; Jianli Jiang; Wenfeng Yao; Quhuan Shen; Jingfu Bao; Ken-ya Hashimoto (Micromachines, 2025)
This article presents an investigation into the use of nanoscale phononic crystals (PnCs) as reflectors for surface acoustic wave (SAW) resonators, with a focus on pillar-based PnCs. Finite element analysis was employed to simulate the phononic dispersion characteristics and to study the effects of the pillar shape, material and geometric dimensions on achievable acoustic bandgap. To validate our concept, we fabricated SAW resonators and filters incorporating the proposed pillar-based PnC reflectors. The PnC-based reflector shows promising performance, even with smaller number of PnC arrays. In this regard, with a PnC array reflector consisting of 20 lattice periods, the SAW resonator exhibits a maximum bode-Q of about 1600, which can be considered to be a reasonably high value for SAW resonators on bulk 42° Y-X lithium tantalate (42° Y-X LiTaO3) substrate. Furthermore, we implemented SAW filters using pillar-based PnC reflectors, resulting in a minimum insertion loss of less than 3 dB and out-of-band attenuation exceeding 35 dB. The authors believe that there is still a long way to go in making it fit for mass production, especially due to issues related with the accuracy of fabrication. But, upon its successful implementation, this approach of using PnCs as SAW reflectors could lead to reducing the foot-print of SAW devices, particularly for SAW-based sensors and filters.